(untitled) (KYAMC Journal, 2020)
Background: Vesico-Vaginal Fistula (VVF) is a major cause for concern in many developing countries with significant morbidity. Among the different techniques abdominal approach of VVF repair is important one. Objective: To find out the outcome of VVF repair by abdominal approach. Materials and Methods: It is a prospective study. Twenty-three patients with VVF were operated with abdominal approach from the period of January 2016 to January 2019. Age of patients, co-morbidities, cause, size and location of VVF were evaluated. Then abdominal approach of VVF repair was done. Operative time and need of blood transfusion were encountered. Post operative (POD) urine leakage, wound infection or other complications were enlisted. Patients were discharged with keeping urethral catheter for 14 days. Follow up was done after 1 and 3 month and in each follow up history and physical examination was done. All collected data were evaluated. Results: Mean age of the patient was 40 years. Among the 23 patients 12 (52%) patients had history of total abdominal hysterectomy, 9 had history of caesarian section and 2 cases had history of pelvic surgery. VVF repair was done at least 12 weeks after its occurrence. Operative time ranged from 90 minutes to 150 minutes. In the immediate POD no obvious complications were noted except one patient developed wound infection on 7th POD. Follow-up done as per schedule and no recurrence of VVF noted. Conclusion: VVF repair through abdominal approach is a feasible, safe and effective technique if performed meticulously. KYAMC Journal Vol. 11, No.-3, October 2020, Page 129-132